Effect of Fe doped on superhydrophilic properties and antibacterial activity of TiO2 thin film preparared by sol-gel dip coating - Lan Anh, Luu Thi; Tuyet Mai, Nguyen Thi; Anh, Trinh Xuan; Chinh, Huynh Dang; Dung, Ta Ngoc; Lam, Tran Dai; Trung, Nguyen Ngoc; Son, Vo Thach (Vietnam Journal of Chemistry, 2014)
In this paper, we present some studies Fe undoped and doped on TiO2 thin ﬁlms is prepared by sol-gel dip coating technique. Effects of doped iron on the characteristics of the ﬁlms were studied using RAMAN spectra. Morphology surface of thin film are investigated by FESEM. Superhydrophilic properties and antibacterial activity of modiﬁed TiO2 ﬁlms were evaluated by studying under visible light and UV irradiation. The superhydrophilic efficiency of modiﬁed TiO2 ﬁlms by this method is affected by the concentration of doped iron. Keywords: Sol-gel dip coating, Superhydrophilic, Antibacterial, Visible light, UV irradiation.